The WT1/MVP-Mediated Stabilization on mTOR/AKT Axis Enhances the Effects of Cisplatin in Non-small Cell Lung Cancer by a Reformulated Yu Ping Feng San Herbal Preparation - Lou, Jian-Shu; Xia, Yi-Teng; Wang, Huai-You; Kong, Xiang-Peng; Yao, Ping; Dong, Tina T. X.; Zhou, Zhong-Yu; Tsim, Karl W. K. (Frontiers in Pharmacology, 2018)
Chemo-resistance is an obstacle in therapy of lung cancer. Alternative therapy of using herbal medicine has been proposed to resolve this obstacle. Yu Ping Feng San (YPFS), a common Chinese herbal medicinal mixture, has been reported to show anti-drug resistance on cisplatin (DDP), a common lung cancer drug. To optimize the anti-cancer function of YPFS, different Chinese herbal extracts having known function to overcome lung cancer were screened in combining with YPFS, as to increase the efficacy of DDP in drug resistance lung cancer cell, A549/DDP. Amongst these herbal extracts, Ginkgo Folium exhibited the most promoting sensitized effect. This revised herbal formula, named as YPFS+GF, promoted the DDP-induced toxicity by over 2-fold as compared to that of YPFS alone; this potentiation was confirmed by inducing cell apoptosis. The anti-drug resistance of YPFS, triggered by an increase of intracellular concentration of DDP, was accompanied by an increased expression and activity of WT1, which consequently decreased the transcript level of MVP. In addition, the MVP-mediated downstream effector mTOR2/AKT was disrupted after application of YPFS+GF in DDP-treated A549/DDP cell: this disruption was characterized by the decline of mTORC2 components, e.g. Rictor, p-mTOR, as well as the phosphorylation level of its downstream protein AKT. The disruption on mTORC2/AKT could be reversed by mTORC2 inducer insulin and promoted by mTORC2 inhibitor PP242. Thus, the anti-drug resistance of YPFS+GF in DDP-treated lung cancer cells might be mediated by the down regulation of WT1/MVP axis, as well as the downstream anti-apoptotic pathway of mTORC2/AKT signalling. Herbal medicine is one of the main adjuvant therapies in non-small cell lung cancer, and this novel herbal formula supports the prescription of traditional Chinese medicine in cancer treatment.